The theological dimensions of F.W.J. Schelling's theory of symbolic language - Whistler, D (2011)
In this thesis I examine Schelling’s construction of symbolic language in §73 of his Philosophie der Kunst. I approach this construction in three ways. First, I compare Schellingian symbolic language to other contemporary theories of the symbol and language (in particular, those of Goethe, Kant and A.W. Schlegel). While Schelling’s theory of symbolic language possesses properties similar to these other theories (the identity of being and meaning, organic wholeness, the co-existence of opposites), I show that it differs in how they are interpreted. Second, I excavate the metaphysical and epistemological principles from Schelling’s philosophy of the period which underlie this theory of language. Three tenets from the Identitätssystem (as it is called) are crucial: formation, quantitative differentiation and construction. They illuminate why Schelling interprets symbolic language very differently to his contemporaries. Third, I consider the theological significance of Schellingian symbolic language. This significance is twofold. First, his theory gives rise to a conception of discourse without reference, and so to the notion of a theology without reference. On this basis, Schelling criticises Christian theology for remaining too concerned with referring to God, when what is at stake is rather the degree of intensity to which it produces God. Theology therefore stands in need of reformation. Second, the way in which theology is utilised by Schelling in order to construct symbolic language in §73 of the Philosophie der Kunst itself provides a model for reformed theological practice. I argue that Schelling conceives of traditional theology as material for intensifying the production of God. In this way, an ‘absolute theology’ is engendered which has no concern for reference or for the integrity of the theological tradition.